A Study on the Applicability of HSPF Paddy-RCH for Calculating the Reduction of Agricultural Non-point Pollutants - Shin Hye Jung; Han-Pil Rhee; Ha Sun Hwang; Chun Gyeong Yoon (대한환경공학회지, 2020)
Objectives:Non-point source pollution (NPS) reduction has been considered as the first priority in South Korea to achieve acceptable water quality. Among many NPS pollutions, agricultural NPS is one of the major NPS contributor due to its vast area. However, agricultural NPS characterization has not been successful because agricultural NPS has inconsistent water and mass balances, thus has lacking NPS reduction measures. This study assesses applicability of HSPF Paddy-RCH method to estimate agricultural NPS loads in paddy rice field. Methods:HSPF Paddy-RCH method was developed to simulate water and mass balance in paddy rice field(s). Applicability of the developed method was tested in Gyeseongcheon watershed in Nakdong River basin, South Korea. The study area was selected because there is no other major pollutant source except the paddy fields, but has simple drainage system. HSPF Paddy-RCH method was calibrated in control paddy field with conventional fertilizing condition and applied to two small scale paddy fields (89% and 76% fertilizing condition). The calibrated HSPF Paddy-RCH method was then tested in small watershed (subbasin) including small paddy fields applied earlier for applicability study of watershed scale. Results and Discussion:Calibrated HSPF Paddy-RCH method well represented observed flow rates (R2=0.825) and water-quality (BOD, T-N, T-P, relative differences [%diff]<7.52%). Water-quality parameters for the control paddy field showed slower decaying rate than river and stream. The calibrated HSPF Paddy-RCH well represented water and mass balance for the small scale paddy fields with varying fertilizing condition (R2>0.689 for flow rate, %diff<12.20% for water quality), as well as for the small scale watershed with large scale paddy fields (R2>0.693 for flow rate, %diff<19.29% for water quality) could promise. Conclusions:This applicability study results would suggest that HSPF Paddy-RCH method is a feasible tool to quantify agricultural NPS pollution and to develop reduction measured for paddy rice field.